Pengaruh Harga, Promosi dan Kualitas Produk terhadap Keputusan Pembelian pada Marketplac Shopee CV.Kanaya Berkah Mandiri - Abdul Hadi; Afanin Hanani Pribadi; Agustina Dianova (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Online shopping has now become a trend to penetrate society because the price of online shopping has caused a change in behavior among the community, especially in the family sphere. This change in behavior can be seen from the shopping habits of customers who previously shopped directly at the market or at the nearest mall, whereas now they prefer to shop directly at the market or at the nearest mall. likes shopping online. Moreover, with online shopping applications, we can see various kinds of goods and can buy them using the internet without having to leave the house or go to the shop in person. This is what causes the online shopping trend to be very popular in Indonesia today. The research aims to determine the influence of price, promotion and product quality on purchasing decisions on the Shopee CV. Price has a 25.1% influence on purchasing decisions. The Promotion variable has an influence of 0252 on purchasing decisions for Kanaya children's clothing consumers in the Shopee marketplace with a significant value of 0.000. Promotion has an influence of 36.9% on purchasing decisions. The product quality variable has an influence of 0.210 on purchasing decisions for Kanaya children's clothing consumers in the Shopee marketplace with a significant value of 0.001. Product quality has an influence of 29.1% on purchasing decisions. This means that an increase or decrease in the Product Quality factor will increase or decrease the Purchasing Decision of Kanaya Children's Clothes consumers in the Shopee marketplace. Promotion has the largest beta value, namely 0.369 or 36.9% of the Purchasing Decision of Kanaya Children's Clothes consumers in the marketplace. Shopee This means that the promotion factor has the greatest influence on purchasing decisions for Kanaya children's clothing consumers in the Shopee marketplace.